Spatiotemporal Distribution and Evolution of Global World Cultural Heritage, 1972–2024 - Yangyang Lu; Qingwen Han; Zheng Zhang; Zhong Sun; Jian Dai (ISPRS International Journal of Geo-Information)
Taking 992 world cultural heritage (WCH) sites as the research object, the spatial distribution and evolution characteristics of WCH were analyzed by kernel density analysis, mathematical statistics, standard deviation ellipse, among other methods, and nine correlation factors were selected to explore the mechanism underlying the spatial and elevation-dependent distribution patterns of WCH and their sensitivity to climate change by using geographic detectors and multi-scale geographically weighted regression (MGWR) models. The results show the following: (1) The spatial distribution type of WCH is aggregation, and 80% of WCH are clustered below 500 m, with Europe and Asia-Pacific as the primary hotspots. (2) The distribution of WCH tends to be global and in the direction of “W-WN” to “E-ES”, and the average center movement direction is “E → EN → ES → E”. There is a trend of positive east–west distribution on the whole. (3) Road density, per capita GDP, and other factors are the dominant factors affecting the spatial pattern of world cultural heritage, and the interaction between the factors shows a nonlinear enhancement or two-factor enhancement trend. (4) There are spatial differences in the mechanisms of the factors, with river density contributing positively, aspect rate and forest cover contributing negatively, population density, per capita GDP, and road density mainly contributing positively to the spatial distribution of the WCH, annual precipitation mainly contributing negatively, and the positive and negative effects of altitude and GDP being comparable. Based on the above-mentioned differences in spatial distribution, evolutionary characteristics, and mechanism of action, the causes are discussed, and some suggestions for developing and protecting the world cultural heritage are presented.